Body composition of table tennis players: comparison between performance level and gender - Zagatto, Alessandro Moura [UNESP] (2016)
The purpose of this study was to compare whole-body and segmental body composition variables of trained Brazilian table tennis players, according to different performance levels and gender. Sixty-four table tennis players (45 male and 19 female) were distributed in three groups according to performance level: international level players (ILP; 12 male; 8 female), national level players (NLP; 14 male; 6 female) and regional level players (RLP; 19 male; 5 female). The anthropometry measurements and body composition analysis were performed using Dual energy X-ray absorptiometry. Male players demonstrated higher fat-free mass (FFM), and lower fat mass (FM) and body fat percentage (%BF, p < 0.05) compared to female players in all competitive levels, however, non-significant differences were found between whole-body composition and performance level. In the comparison between the dominant and non-dominant arms, FFM, fat-free soft tissue mass (FFSTM) and bone mineral density (BMD) were higher in the dominant arm (p < 0.05) compared to the non-dominant arm in all competitive levels, however, the male ILP group presented lower FFM and FFSTM in the dominant arm compared to the NLP, while the female ILP group presented higher BMD compared to the NLP and RLP. In conclusion, male table tennis players presented higher FFM and lower FM and %BF than female players and the dominant arm presented higher FFM and BMD than the non-dominant, possibly due to the mechanical impact-load imposed by time of table tennis practice.